Andrea Fraser - Inaugural speech - Fraser, Andrea 1965- ([Andrea Fraser], 1997)
"Inaugural Speech documents Andrea Fraser's live performance at the opening of the exhibition inSITE97 in San Diego, California. Following official speakers reading letters from U.S. and Mexican presidents Clinton and Zedillo, Fraser takes the podium to deliver five speeches rolled into one. Addressing the audience first as an artist, then as an exhibition organizer, then as a trustee, as a public official, and finally as a corporate sponsor, Inaugural Speech looks at the pyramid of power for which artists and art audiences form the base of support. Introducing herself with each "speech" and then thanking herself for the generous introduction, Fraser implodes the rituals of mutual recognition and legitimation that cement the collusion of often conflicting interests in the field of contemporary art"
"Videotapes by Andrea Fraser."--Container ; "Inaugural Speech documents Andrea Fraser's live perforamnce at the opening of the exhibition InSITE97 in San Diego, California."
Keywords: Fraser, Andrea -- 1965-; Geschichte 1997; Aufführung; Arts and society / History / 20th century; Arts, Modern / 20th century; Speeches, addresses, etc / Parodies, imitations, etc; Performance art / United States; Conceptual art / United States; Arts and society; Arts, Modern; Conceptual art; Performance art; Speeches, addresses, etc; United States; 1900-1999; History; Parodies, imitations, etc; Film; DVD-Video